Faktor Meningkatnya Angka Perceraian di Kabupaten Aceh Singkil - ., Hasmida (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
The principle of a marriage of Islam is forever, so all efforts must be made so that the marriage bond can continue. However, marriage travel is not always as smooth as it is desired since problems must be encountered that sometimes arise from unheard of directions. If the problem can not be solved, then lead to divorce, divorce itself is the last resort to live. The Syar'iyah Aceh Singkil Court has received, examined and severed every case that came against it, especially the divorce case which is the highest cause of 301 cases from 2014-2016 and continues to increase. Looking at the data the authors are interested in examining the factors that influence the high rate of divorce in the Syar'iyah Aceh Singkil Cour. The results showed that the factors that influence the high number of divorce account that is the absence of harmony in the household, no responsibility husband and wife, low economic, low level of education, moral crisis, third party interference and polygamy unhealthy. Divorce factors are in the background behind the low spiritual and emotional aspects, economic aspects, aspects of education and aspects of the times.